PEDAGOGICAL PSYCHOLOGICAL VIEWS OF ABU RAIKHAN BERUNI AS A FACTOR OF EFFECTIVENESS IN THE EDUCATIONAL PROCESS (World Bulletin of Management and Law, 2023)
This article reveals the importance of developing a spiritual culture among young people using the views of Abu RayhanBeruni on the upbringing of a healthy generation that characterizes today's globalization process.
Keywords: family; healthy; educational process; inheritance